Effects of Meteorin-Like Protein on Pain in an Experimental Diabetes Model - Yuksel, Furkan; Tekin, Suat; Ozcan, Mete; Sandal, Suleyman (Wiley, 2023)
[Abstract Not Available]
Keywords: Pain; Diabetes; METRNL; Neuropathy